Mapping Circular Economy Adoption in Multinational Enterprises: Industry-Wise Barriers and Future Directions - Bhanderi, Jay; Chawla, Yash (Mapowanie wdrażania gospodarki o obiegu zamkniętym w przedsiębiorstwach międzynarodowych: bariery branżowe i przyszłe kierunki, 2025)
Aim: This article investigates the uneven adoption of circular economy practices across industrial sectors, with a focus on how and why some industries progress more rapidly than others. Special attention is given to the role of multinational enterprises as enablers of circular transitions, examining the systemic and organizational factors that influence implementation outcomes. Methodology: A structured qualitative literature review was conducted, drawing on peer-reviewed academic sources published between 2015 and 2024. The analysis applied a multi-level framework, macro (industry and policy context), meso (supply chain and ecosystem coordination), and micro (firm-level strategies) to compare circular economy adoption across six major industries: automotive, electronics, manufacturing, food and beverage, construction, and textiles. Results: The findings reveal three distinct tiers of circular economy maturity. High-adoption industries such as automotive and electronics, have embedded circularity through strategic leadership and supply chain integration. Medium-adoption sectors exhibit promising initiatives, even though progress remains fragmented. Low-adoption industries face persistent regulatory, infrastructural, and cultural barriers that inhibit systemic change. Across sectors, the interaction of regulatory, economic, technological, and organizational factors creates compounded challenges to circular economy implementation. Implications and recommendations: Effective circular economy adoption requires coordinated efforts to overcome structural barriers and build enabling capabilities. Policymakers should design sector-specific support mechanisms and promote cross-sector learning. Organizations are encouraged to institutionalise a circular economy through dedicated leadership, capability development, and supply chain innovation. Future research should focus on developing a circular economy adoption maturity model that integrates industry-specific dynamics with actionable implementation pathways. Originality/value: This review offers a novel synthesis of a circular economy adoption patterns across industries, advancing theoretical insight and practical guidance. By comparing divergent sectoral experiences, the paper contributes to a conceptual framework for understanding circular economy readiness and strategic levers for change.
Ekonomia XXI Wieku = Economics of the 21st Century, 2025, Nr 28, s. 40-51
Keywords: circular economy; industry adoption patterns; multinational enterprises; implementation barriers; sustainability transition; gospodarka o obiegu zamkniętym; wzorce wdrażania w przemyśle; przedsiębiorstwa wielonarodowe; bariery wdrażania; transformacja w kierunku zrównoważonego rozwoju